Effect of traditional Chinese medicine formula GeGen decoction on primary dysmenorrhea: A randomized controlled trial study. (28th October 2020) - Chai, Chengzhi; Hong, Fang; Yan, Yan; Yang, Lu; Zong, Hui; Wang, Changsong; Liu, Zhigang; Yu, Boyang
Abstract: Ethnopharmacological relevance: GeGen Decoction, a well-known Chinese herbal formula, is widely used in China and other Asian countries to treat gynecological diseases, including primary dysmenorrhea. Pharmacological studies have confirmed that GeGen Decoction is able to inhibit spasmodic contractions of the uterus in vivo and in vitro. Aim of the study: The objective of this study is to examine the efficacy and safety of GeGen Decoction on primary dysmenorrheic patients. Methods: This was a randomized, double-blinded, placebo-controlled trial. GeGen Decoction or placebo was administered a week before the expected start of each cycle for three consecutive menstrual periods. Between-group differences in pain intensity were detected by visual analogue scale (VAS). In addition, serum levels of arginine vasopressin (AVP) and estrogen (E) were examined by enzyme-linked immunosorbent assay. Metabolomic analysis was further used to evaluate the influence of GeGen Decoction on the metabolomics of primary dysmenorrheic patients. Results: A total of 71 primary dysmenorrheic women were recruited and 30 participants met the criteria were randomized into GeGen Decoction or placebo group. After three consecutive menstrual cycles' treatments, the VAS score of the GeGen Decoction group was significantly lower than that of the placebo group. Both serum levels of AVP and E decreased after GeGen Decoction administration, while the placebo seemed to have little effect on either of the index. Moreover, after GeGen Decoction treatment, seven important metabolites were identified by metabolomic analysis compared to the placebo group. No abnormalities in blood biochemical and routine physical examination pre and post GeGen Decoction intervention were observed. Conclusions: GeGen Decoction can remarkably relieve the severity of menstrual pain without obvious adverse effects. Its therapeutic effect on primary dysmenorrhea might be related to the regulation of pituitary hypothalamic ovarian hormones, and interfering with the metabolic change. Graphical abstract: Image 1